Effect of Metakaolin on the Corrosion Resistance of Strcutural Lightweight Concrete - Keleştemur, Oğuzhan; Demirel, Bahar (My University, 2015)
In this study, the mechanical and physical properties of structural lightweight concrete (SLC) specimens produced by substituting cement with metakaolin (MK) at ratios of 5%, 10%, 15% and 20% w/w were examined, and the corrosion behavior of the reinforcing steel bars embedded in these specimens was investigated. Corrosion rates of the bars were determined by using galvanic current measurement method. Furthermore, the corrosion potential of the steel bars in these specimens was measured daily for a period of 90 d based on ASTM C876 standard test method. As a result of this study, it was found that the MK improved the mechanical and physical properties of the SLC and the 15% w/w MK addition showed the optimum contribution to the strength development. Furthermore, the use of MK in SLC specimens, as a cement replacement up to 15% w/w, improved the corrosion resistance of the specimens, while there was no positive effect when MK was added in greater ratios. The conclusions were also supported with scanning electron microscope (SEM) studies.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Metakaolin; Corrosion; Structural lightweigth concrete; Microstructure